The Effects of Glyceryl Trinitrate Patch on the Treatment of Preterm Labor: A Single-blind Randomized Clinical Trial - A Nankali; P Kord Jamshidi; M Rezaei (JRI, 2014)
Background: Preterm labor (PTL) is one of the main causes of neonatal mortality and morbidity. PTL leads to serious complications especially in the gestational age prior to 24-26 weeks. The aim of this study was to investigate the effect of glyceryl trinitrate (GTN) patch on the treatment and complications of PTL. Methods: In this clinical trial, 84 singleton pregnant women with gestational age of 27-35 weeks were surveyed. PTL was clinically diagnosed and the patients were randomly divided into two groups who were treated with GTN or placebo for 48 hr. The consequences, complications and changes in some parameters in both groups were compared. Data were analyzed with chi square test, paired and unpaired t tests by SPSS software and p<0.05 was considered significant. Results: No significant difference was observed between two groups in terms of successful tocolysis, receiving full dose of corticosteroids and the mean prolongation of the pregnancy. However, delivery times in patients who delivered during the hospitalization were 31±4.4 and 18.3±2.2 hr (p=0.01), respectively. Headache was more severe in control group (p=0.007). The systolic and mean arterial blood pressure decrease (p<0.001) and maternal heart rate increase (p=0.01) were significant in GTN group. The changes of vital signs were not significant in placebo group. Conclusion: The effect of GTN in the treatment of PTL is similar to the placebo without any serious complication. However, GTN delays the delivery time in delivery during the primary hospitalization. Thus, further studies with larger sample size are needed to evaluate the exact effects of GTN on PTL.